ID: 113. Issue 1 (November 2015) - Lin, Rongtuan; Liu, Yiliu; Belgnaoui, Sidi Mehdi; Sze, Alexander; Goulet, Marie-Line; Zheng, Chunfu
<x xml:space="preserve">Abstract</x> RIG-I is essential for recognizing RNA viruses with a 5' triphosphate (ppp) signature in the cytoplasm. Upon viral RNA recognition, RIG-I recruits adaptor protein MAVS to trigger the activation of IRF3 and NF-kB transcription factors, leading to activation of antiviral response. STING has been identified as an RIG-I signaling cofactor and a critical adaptor protein required for cytosolic DNA and cyclic dinucleotides (CDNs) triggered immune responses. We have identified STING among a plethora of differentially expressed genes induced by the 5'ppp RNA; in the present study, we further detail the mechanism of STING regulation. Our data shows that virus infection induces STING expression at both the mRNA and protein levels. Furthermore STING induction is shown to be dependent on functional RIG-I signaling. STING induction by the RIG-I agonist 5'ppp RNA was recognized as a delayed event resulting from an autocrine/paracrine mechanism. Indeed, co-treatment with TNFα and IFNα has a synergistic effect on the regulation of STING expression. Depletion of STAT1 and RELA, either individually or combined, significantly diminished virus-induced STING protein expression compared with the cells. In A549 cells, the expression of interferon-response/inflammatory response genes was not affected in the absence of STING at early time points, but was significantly reduced at late time points. Furthermore, our results also unveiled an essential contribution of STING in the establishment of the 5'pppRNA induced antiviral responses during HSV1 infection. Taken together, these observations demonstrate that the STING is induced via RIG-I signaling and up-regulated STING is essential for 5'ppp RNA mediated HSV restriction.